Study of the Law on Child Protection from Cases of Verbal Violence Against Children - Apud Abdul Aziz; Junifer Dame Panjaitan (MultiTech Publisher, 2023)
Cases of violence against children in the modern era are currently very common. Cases of violence against children are committed by adults. Law enforcement for someone who is confronted needs to be done for the sake of upholding the law. An action committed against violence against children has a cause which is the background to why the action was carried out. This is where the important role of criminology is in knowing why someone commits a crime and how to overcome the crime problem. The role of the family and society is very important to monitor violence against children.